Temporal trends in antithrombotic treatment of real-world UK patients with newly diagnosed atrial fibrillation: findings from the GARFIELD-AF registry - Apenteng, P; Gao, H; Hobbs, F; Fitzmaurice, D (BMJ Publishing Group, 2018)
Objective To investigate evolving patterns in antithrombotic treatment in UK patients with newly diagnosed non-valvular atrial fibrillation (AF). Design Prospective, multicentre, international registry. Setting 186 primary care practices in the UK. Participants 3482 participants prospectively enrolled in four sequential cohorts (cohort 2 (C2) n=830, diagnosed September 2011 to April 2013; cohort 3 (C3) n=902, diagnosed April 2013 to June 2014; cohort 4 (C4) n=850, diagnosed July 2014 to June 2015; cohort 5 (C5) n=900, diagnosed June 2015 to July 2016). Participants had newly diagnosed non-valvular AF and at least one risk factor for stroke, were aged ≥18, and provided informed consent. Main outcome measures Antithrombotic treatment initiated at diagnosis, overall and according to stroke and bleeding risks. Stroke risk was retrospectively calculated using CHA2DS2-VASc (cardiac failure, hypertension, age ≥75 (doubled), diabetes, stroke (doubled)–vascular disease, age 65–74 and sex category (female)) and bleeding risk using HAS-BLED (hypertension, abnormal renal/liver function (1 point each), stroke, bleeding history or predisposition, elderly (>65), drugs/alcohol concomitantly (1 point each)). Results 42.7% were women and the mean age was 74.5 years. The median CHA2DS2-VASc score was 3 in all cohorts and the median HAS-BLED score was 2 in all cohorts. There was a statistically significant increase in the use of anticoagulant therapy from C2 to C5 (C2 54.7%, C3 60.3%, C4 73.1%, C5 73.9%; P value for trend <0.0001). The increase in the use of anticoagulant was mainly in patients with CHA2DS2-VASc ≥2. The use of vitamin K antagonists (VKAs)±antiplatelet (AP) drugs decreased from C2 to C5 (C2 53.3%, C3 52.1%, C4 50.3%, C5 30.6%), while the use of non-vitamin K antagonist oral anticoagulants (NOACs)±AP increased (C2 1.3%, C3 8.0%, C4 22.7%, C5 43.3%). The use of AP only decreased (C2 36.4%, C3 25.5%, C4 11.9%, C5 10.5%), as did the combination therapy of VKA+AP (C2 13.6%, C3 11.0%, C4 9.6%, C5 5.8%). Conclusion There has been a progressive increase in the proportion of patients newly diagnosed with AF receiving guideline-recommended therapy in the UK, potentially driven by the availability of NOACs.